Enhancing Elementary Students’ Learning Outcomes on Force Concept through Interactive Learning - Titi Sriwahyuni; Syaiful Hidayat; Karmila Risa Rahmawati; Irawati Irawati; Sofia Anastasya; Rusni Syahril (Horizon of Primary Education, 2025)
This study aims to observe the enhancement of student learning outcomes in Class IV A at SD Negeri Pembina Tolitoli through the implementation of more interactive learning methods. The primary focus of this research lies in comprehending force-related materials. Employing the Kemmis and Mc. Taggart model, the research was carried out in the odd semester of the school year, specifically in October. The study involved 34 students as subjects, with particular emphasis on their grasp of force-related materials. The collected data underwent descriptive analysis and was presented in tabular format. The findings indicated a notable improvement in students' comprehension of the material. In the initial cycle, the average score stood at 44.12, while in the subsequent cycle, it surged to 86.99. This outcome affirms that employing an interactive learning approach centered around educational games in IPAS lessons can significantly enhance student understanding in Class IV A at SD Negeri Pembina Tolitoli.